For non-empty sets A and B, if A ⊂ B then (A × B) ∩ (B × A) is equal to
Answers
Answer:
see ur answer!!!
Step-by-step explanation:
If A & B are two non- empty subsets and we have to prove AxB=BxA iff A=B
Proof:
We will prove this in two parts. In first part we will prove that if A=B then AxB=BxA and in the second part we will prove that if AxB=BxA then A=B.
i) For the first part let us assume that A=B
Then in AxB we can first replace first ‘A’ with ‘B’ (As by assumption A=B) so that it becomes BxB. Now we have AxB=BxB. In the next step we replace ‘B’ with ‘A’ so that BxB can be written as BxA.
Thus we have AxB=BxB=BxA
ii)For the second part we assume that AxB=BxA and then we will prove that A=B. We will prove this by double containment. We will prove that A is subset of B and then B is subset of A .
Let x∈ A and y∈B
Now (x, y) ∈ AxB
But by our assumption AxB and BxA are equal
So (x,y) ∈ BxA implying that x ∈B , sine x is an arbitrarily chosen element, so A is subset of B.
Now let x∈B and y∈A
So (x,y) ∈ BxA
But again since BxA=AxB; therefore x∈A. Thus implying as before that Bis subset of A
Thus from double containment viz. A being subset of B and B being subset of A; we get A=B.
Thus (i) and (ii) complete the proof.
Mark as brainalist....
Answer:
For non-empty sets A and B, if A ⊂ B then (A x B) ∩ (B x A) is equal to :
A = B.
Step-by-step explanation:
If A and B are two non-empty subsets, and if A=B, then we must demonstrate that AxB=BxA.
Proof – There are two elements to our argument. We shall demonstrate in the first section that if A=B, then AxB=BxA, and in the second section, that if AxB=BxA, then A=B.
Considering that A=B, let's go on to part one.
Then, in AxB, we can first swap out the initial "A" with "B" (on the assumption that A=B), resulting in BxB. Since then, AxB=BxB. In the following step, "B" is changed to "A" so that BxB can be written as BxA.
This gives us AxB=BxB=BxA.
In order to prove that A=B in the second section, we shall make the assumption that AxB=BxA. We'll use double confinement to demonstrate this. We will demonstrate that A is a subset of B, after which B is a subset of A.
Suppose xe A and ye B
Here, (x, y) E AXB
However, based on our presumption, AxB and BxA are equal.
Given that x is a randomly chosen element and that (x,y) E BxA implies that x EB, A is a subset of B.
Let EB and vEA now.
So (x,y) E BxA
However, as BxA=AxB once more, EA follows. As before, this implies that Bis is a subset of A.
A=B is the result of double containment, where A is a subset of B and B is a subset of A.
#SPJ3